A case of delayed exacerbation of interstitial lung disease after discontinuation of temsirolimus. (2017) - Matsuki, Rei; Okuda, Kenichi; Mitani, Akihisa; Yamauchi, Yasuhiro; Tanaka, Goh; Kume, Haruki; Homma, Yukio; Hinata, Munetoshi; Hayashi, Akimasa; Shibahara, Junji; Fukayama, Masashi; Nagase, Takahide
Abstract: Temsirolimus is an inhibitor of mammalian target of rapamycin and interstitial lung disease (ILD) is known to be one of the adverse events associated with temsirolimus, which usually improves rapidly after discontinuation of the drug and rarely worsens thereafter. Herein, we report a case of delayed exacerbation of ILD after discontinuation of temsirolimus for metastatic renal cell carcinoma in an 86-year-old male with chronic ILD. The patient developed gradually worsening dyspnea five weeks after an initiation of temsirolimus and was admitted to our facility. On his admission, although a pulmonary function test revealed a decreased diffusion capacity, there was no obvious progression of ILD on HRCT scan. His dyspnea once improved after discontinuation of temsirolimus, but it recurred and acute exacerbation of ILD was diagnosed 40 days after his last administration of temsirolimus. He received high-dose steroid therapy, however, he deteriorated and died. Histopathological examination of the lungs at autopsy revealed overlapping diffuse alveolar damage with chronic interstitial changes. In the present case, since there were no specific factors that could have caused acute exacerbation of ILD except for temsirolimus, it was considered to contribute to the exacerbation of underlying ILD. In conclusion, physicians should be aware of the possibility of temsirolimus-induced ILD not only while the medication is administered, but also even after it is discontinued. It is important to carefully interview the patient and to recognize the value of physiological tests, such as respiratory function tests and blood gas analysis, as well as imaging findings on HRCT.